The Effect of Shadow Banking on the Systemic Risk in a Dynamic Complex Interbank Network System. (18th May 2020) - Fan, Hong; Pan, Hongjie
Abstract : After the financial crisis triggered by the subprime mortgage crisis in the United States in 2008, many scholars believed that the unstable transmission of shadow banking business in the banking system is the main factor causing financial turmoil. This paper proposes a dynamic complex interbank network system model with shadow banking in which the dynamic complex interbank network system differs from the traditional banking network and is formed by the interrelated business between shadow banks and commercial banks to explore the effect of shadow banking on the systemic risk. The results show that the existence of shadow banking will increase the systemic risk, accelerate the speed of bankruptcy of banks, reduce the survival ratio of banks, and increase the strength of central bank assistance. The smaller the number of shadow banks in the system, the higher the degree of credit connection among commercial banks and the smaller the systemic risk.